Nature protection across countries: Do size and power matter? - Baldi, Germán (2020)
Protected areas are one of the most effective tools for nature conservation. Consequently, almost all countries have agreed to set increasingly demanding goals for the expansion of their protected area systems. However, there is a large disparity among countries, and research on the cultural drivers of differences remains quite unexplored. Here, we analyze the relationship between the protected extent and a limited spectrum of socio-economic characteristics, making focus on size and power features. Protected areas under strict conservation categories (I to IV, IUCN) were considered for 195 countries, and relationships were modeled by means of LOESS regressions, violin plots, and a random forest ensemble learning method. Larger and more powerful countries (in terms of land area, gross domestic product, or military expenditure) protect less and in relatively smaller units than smaller and less powerful countries. Out of the twenty most extensive countries of the world, only two exceed 10 % of protection. This situation is problematic since an effective growth of the global protected area network depends on the willingness of larger and more powerful countries. We propose different hypotheses a posteriori that explain the role of size and power driving protection. These hypotheses involve direct mechanisms (e.g., the persuasive capacity of large countries) or mechanisms that mediate the interactions of some others (e.g., tourism contribution to GDP and insularity). Independently of mechanisms, our results emphasize the conservation responsibilities of large and powerful countries and contribute envisioning conservation scenarios in the face of changes in the number and size of countries.